Designer probiotics for the prevention and treatment of human diseases. (October 2017) - Chua, Koon Jiew; Kwok, Wee Chiew; Aggarwal, Nikhil; Sun, Tao; Chang, Matthew Wook
Highlights: Recent developments in engineered probiotic therapeutics for a variety of human diseases were reviewed. Advantages of engineered probiotics as drug delivery systems over traditional therapies were discussed. Current obstacles and future perspectives of engineered probiotic therapeutics were discussed. Abstract : Various studies have shown the beneficial effects of probiotics in humans. The use of synthetic biology to engineer programmable probiotics that specifically targets cancer, infectious agents, or other metabolic diseases has gained much interest since the last decade. Developments made in synthetic probiotics as therapeutics within the last three years will be discussed in this review.